PENGARUH LIVE STREAMING DAN PERSEPSI HARGA TERHADAP MINAT BELI YANG DIMEDIASI OLEH BRAND AWARENESS PADA PRODUK DJL.STAR DI KOTA BANDUNG - Sella Dwi Ayu Fatimah; Frido Saritua Simatupang (ITB AAS Indonesia Surakarta, 2024)
Imported snacks are among the food and beverage items that are quite popular among the public, yet their sales remain relatively rare, necessitating further study. This research aims to investigate the influence of live streaming and price perception on purchase interest, mediated by brand awareness for DJL. Star products in Bandung City. The methodology employed in this study is a quantitative approach, utilizing data collection techniques through questionnaires distributed to respondents via social media platforms Instagram and WhatsApp, selected using purposive sampling. Data analysis is conducted using instrument tests, classical assumption tests, path analysis, Sobel tests, and hypothesis testing. The population targeted in this study consists of online shoppers in Bandung City, with a sample size of 100 individuals analyzed using SPSS software. The results indicate that live streaming (X1), price perception (X2), and brand awareness (Y) positively influence purchase interest (Z). Brand awareness doesn’t mediates the effect of live streaming (X1 on purchase interest (Z), but brand awareness mediates the effect of price perception (X2) on purchase interest (Z). Keywords : Live Streaming, Price Perception, Purchase Interest, Brand Awareness